Fabrikasi Pandu Gelombang Lima Lapis Berbasis Polimer Polystyrene (PS) dan Polymethyl Methacrylate (PMMA): Faridawati, Sudarsono, dan Yono Hadi Pramono - Faridawati, Faridawati; Sudarsono, Sudarsono; Yono Hadi Pramono, Yono Hadi Pramono (Jurnal Fisika dan Aplikasinya, 2025)
Fabrication of five-layer waveguides with slab structur based on polymer materials polystyrene (PS) 3% and polymethyl methacrylate (PMMA) 2% using the spin coating method has been carried out. The composition of five-layer waveguides were polystyrene as film with a refractive index 1.59 and PMMA as cover and gap with refractive index of 1.49. Based on the results obtained thickness 7.4µm fabrication for polystyrene film and 10.93µm for PMMA as a cover and 4.84µm for PMMA as a gap. Two waveguides are expected to be used as a directional coupler.